Fauna associated with pelagic Sargassum in the Gulf Stream - Weis, J. S.
The fauna associated with samples of Sargassum collected from the Gulf Stream has been identified, analyzed, and compared with that reported by other workers from samples collected from the Sargasso Sea. Notable in the present collections are two species of small gastropods not previously reported. The possible significance of these gastropods, as consistent with a benthonic origin of the Gulf Stream Sargassum, is discussed
Keywords: FAUNA; PELAGIC SARGASSUM; GULF STREAM